Radical Scavenging, Preliminary Phytochemical Screening and DNA Protective Effect of Carissa Carandas Linn Plant Leaves - Swathi K Amaranath; Dr. Nagarathna Amresh; Dr.Kiruthika Balasubramanian (International Journal of Pharma and Bio Sciences, 2021)
Free radicals (ROS) are highly reactive and unstable compounds. In a normal cell there is a balance between formation and removal of free radicals. However, this balance can be shifted towards the formation of more free radicals, when levels of antioxidants are diminished. This oxidative stress can result in oxidative damage to cellular components such as DNA, proteins and lipids etc which act as a mediator of pro-inflammatory and carcinogenic events. The free radical scavengers prevent formation of reactive species or remove them before they can damage vital components of the cell. Phytochemicals are also important to manage pathological conditions of those diseases caused by free radicals and a large number of phytochemicals exhibit strong inhibitory effects on the broad spectrum of microorganisms. The present study was formulated to study the radical scavenging (H2O2 and hydroxyl) and DNA protective effect of Carissa carandas leaf extracts. Three solvent extracts (Hexane, Ethyl acetate and Isopropanol) were prepared and 100 mg /ml was used for the assay. The results showed that Carissa carandas exhibited strong radical scavenging ability and also showed considerable DNA protective effect under oxidant induced stress conditions. The phytochemical screening was also conducted which revealed the presence of flavonoids, phenols and alkaloids. Various studies showed that flavonoids act as valuable antioxidants because of their chelating properties. Phytochemicals bind to the Fe (II), thus preventing this pro-oxidant cation from reacting with hydrogen peroxide or promote the oxidation of the less stable ferrous complexes into more stable ferric ones (i.e., auto-oxidation) that cannot participate any longer to the Fenton reaction. So, we also conducted a chelating assay and the results revealed that the plant extract also possesses a good chelating effect.